Features of the immune response in children with acute respiratory infections caused by DNA and RNA viruses - O. O. Obukhova; T. I. Ryabichenko; G. A. Skosyreva; O. M. Gorbenko; A. P. Shvayuk (Сибирский научный медицинский журнал, 2022)
The issues of immunopathogenesis of acute respiratory viral infections (ARVI) remain relevant, despite a long history of study. The aim of the study was to investigate the characteristics of the content of some cytokines in the blood serum of children with ARVI caused by DNA and RNA-containing viruses. Material and methods. We examined 92 children with ARVI at the age from 1 to 15 years, hospitalized in the hospital of the Children’s Clinical Hospital No. 6 (Novosibirsk). In order to determine the etiological factor, a study was carried out using the RT-PCR method (test systems AmpliSensORVI-screen-FL, “InterLabService”, Russia) of mucus from the nose and throat for the presence of genetic material of viruses that cause ARVI. Determination of the content of IL-8, IL-17, IFN-γ in the blood serum in children of all groups was carried out by the method of solid-phase ELISA using commercial test systems of LLC “Cytokin” (Russia). Results and discussion. 4 groups were formed: group I (n = 20) children with ARVI caused by DNA-containing viruses (group B, C, E adenoviruses, bocaviruses); group II (n = 53) children with ARVI caused by RNA viruses (RS virus, metapneumovirus, parainfluenza viruses 1, 2, 3, 4, rhinovirus and coronoviruses); group III (n = 12) children with ARVI caused by mixed infection; group IV (n = 7) – the genetic material of the pathogen has not been isolated. Concentration of IL-8, IL-17, IFN-γ was significantly increased in all groups compared to the normative values. Higher values of IFN-γ and IL-8 were revealed in patients with DNA viruses compared with the group with RNA-containing viruses, although the excess of IFN-γ was not statistically significant. Differences in the content of IFN-γ, IL-8 and IL-17 were noted for various etiological viral agents, but they were not significant. Conclusions. The results obtained can serve as confirmation that the functional characteristics of the response of the immune system in children with ARVI are determined not so much by the etiological factor as by its individual state. With ARVI in children, the presence of genetic material from more than one virus, apparently, is not a significant potentiating factor in the activation of the immune response. At the same time, a negative PCR result with a detailed clinical picture of ARVI does not exclude the viral genesis of the disease.